2018
DOI: 10.1016/j.nbscr.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Acute sleep disruption- and high-fat diet-induced hypothalamic inflammation are not related to glucose tolerance in mice

Abstract: Chronic insufficient sleep is a major societal problem and is associated with increased risk of metabolic disease. Hypothalamic inflammation contributes to hyperphagia and weight gain in diet-induced obesity, but insufficient sleep-induced neuroinflammation has yet to be examined in relation to metabolic function. We therefore fragmented sleep of adult male C57BL/6J mice for 18 h daily for 9 days to determine whether sleep disruption elicits inflammatory responses in brain regions that regulate energy balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Various clinical studies have also documented the occurrence of inflammation caused by sleep loss (Siegel, 2005). Recent studies have provided evidence that both chronic sleep loss and fragmentation can activate glial cell types and influence behavioral and physiological states (Graves, 2003;Ho et al, 2018;Wisor et al, 2008). In addition, the activation of the sympathetic nervous system and HPA axis after sleep disturbance leads to a heightened pro-inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Various clinical studies have also documented the occurrence of inflammation caused by sleep loss (Siegel, 2005). Recent studies have provided evidence that both chronic sleep loss and fragmentation can activate glial cell types and influence behavioral and physiological states (Graves, 2003;Ho et al, 2018;Wisor et al, 2008). In addition, the activation of the sympathetic nervous system and HPA axis after sleep disturbance leads to a heightened pro-inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep debt effects on neuroinflammation have been described previously ( 186 ). More recently, Ho et al ( 187 ) verified that sleep fragmentation protocol (18 h of sleep fragmentation per every 24-h period) plus HFD promote microglial activation. Three days of exposure to sleep fragmentation or HFD increased Iba-1-ir (Ionized calcium binding adaptor molecule 1 immunoreactivity) in the arcuate nucleus and the ventromedial hypothalamus.…”
Section: Inflammation Neuroinflammation and Obesity: Relationship Between Diet Sleep And Physical Exercisementioning
confidence: 99%
“…After this initial period, weights remained relatively stable (Fig 3e). Prior studies on sleep disruption reported varied outcomes (e.g., weight loss, no weight change, or weight gain), depending on the experimental paradigm [34][35][36] . In our specific model, weight gain was not a contributing factor to the increase in cellular senescence.…”
Section: Senescence Is Not Due To Weight Gainmentioning
confidence: 99%